A Compact 32-bit Architecture for an AES System - Somsak Choomchuay; Surapong Pongyupinpanich; Somsanouk Pathumvanh (My University, 1970)
This paper describes a compact 32-bit architecture developed for the Rijndael ciphering/deciphering system. The implementation is complied with NIST Advanced Encryption Standard (AES). The design processes any 128-bit block data with 128-bit key. For the compact hardware, the field inversion circuit and the key scheduling circuits are shared by both the encryption and decryption process. The on-the-fly KeyScheduling implementation offers fast processing speed but with core size trade-off. According to the evaluation made on the targeted FPGA, the design can offer the throughput of 768 mbps at 264 MHz clock speed.
Keywords: AES implementations; NIST; Disk encryption hardware; Cryptographic Implementations and Security